Female-to-male sex reversal in mice caused by transgenic overexpression of Dmrt1 - Zhao, Liang; Svingen, Terje; Ng, Ee Ting; Koopman, Peter (Development (Cambridge), 2015)
Genes related to Dmrt1, which encodes a DNA-binding DM domain transcription factor, act as triggers for primary sex determination in a broad range of metazoan species. However, this role is fulfilled in mammals by Sry, a newly evolved gene on the Y chromosome, such that Dmrt1 has become dispensable for primary sex determination and instead maintains Sertoli cell phenotype in postnatal testes. Here, we report that enforced expression of Dmrt1 in XX mouse fetal gonads using a Wt1-BAC transgene system is sufficient to drive testicular differentiation and male secondary sex development. XX transgenic fetal gonads showed typical testicular size and vasculature. Key ovarian markers, including Wnt4 and Foxl2, were repressed. Sertoli cells expressing the hallmark testis-determining gene Sox9 were formed, although they did not assemble into normal testis cords. Other bipotential lineages differentiated into testicular cell types, including steroidogenic fetal Leydig cells and non-meiotic germ cells. As a consequence, male internal and external reproductive organs developed postnatally, with an absence of female reproductive tissues. These results reveal that Dmrt1 has retained its ability to act as the primary testis-determining trigger in mammals, even though this function is no longer normally required. Thus, Dmrt1 provides a common thread in the evolution of sex determination mechanisms in metazoans.